Acid–base controllable nanostructures and the fluorescence detection of H2PO4− by the molecular shuttling of tetraphenylethene-based [2]rotaxanes. Issue 9 (15th February 2021) - Arumugaperumal, Reguram; Shellaiah, Muthaiah; Lai, Yu-Kuang; Venkatesan, Parthiban; Raghunath, Putikam; Wu, Shu-Pao; Lin, Ming-Chang; Sun, Kien Wen; Chung, Wen-Sheng; Lin, Hong-Cheu
Abstract : Aggregation-induced emission (AIE)-active switchable [2]rotaxanes with two arm-terminated TPE units synthesized by click reaction can induce various acid-base controllable nanostructures and exhibit selective detection of H2 PO4 − ion. Abstract : Aggregation-induced emission (AIE)-active switchable [2]rotaxane TR2 with two different molecular stations and arm-terminated TPE units at both ends, and their derivatives were synthesized by means of threading, followed by the stoppering tactic via click chemistry. The AIE behavior of thread A1 and [2]rotaxanes (TR1, TR2, and TR3 ) in CH3 CN were activated by tuning water fractions ( f w ), which induced the development of various well-defined nanostructures including spheres, nanorods, truncated cubes, and nanocubes via the self-assembly of scaffolds. These AIE changes and distinct nanostructures formation verify that the reported analogous rotaxanes were controlled by the shuttling movements of the macrocycle along with wide ranges of multi-non-covalent interactions. The anion-templated construction of [2]rotaxane TR2 with a high level of structurally complex design always encounters more challenging tasks. Evidently, the key to the design involved encoding flexible arms on both triazolium motifs, and exhibited an impressive selectivity and sensitivity (with a detection limit of 0.20 μM) towards the complementary H2 PO4 − ion species. The specific mechanical molecular motion and host–guest interactions of mechanically interlocked molecules (MIMs) were also further explored by quantum mechanical calculations. Importantly, the AIE changes of [2]rotaxanes TR1, TR2, and TR3 were further supported by their bioimaging applications and specifically, [2]rotaxane TR2 could be applied to in vitro imaging with H2 PO4 − at subcellular levels. This flexible multi-component synthetic strategy affords access to the systematic tuning of molecular structures and self-assembled architectures, and it will inspire further studies on the self-assembly of TPE-containing MIMs for materials science and biological applications.